2022
DOI: 10.1200/op.21.00692
|View full text |Cite
|
Sign up to set email alerts
|

Proportion of Early-Onset Gastric and Esophagus Cancers Has Changed Over Time With Disproportionate Impact on Black and Hispanic Patients

Abstract: PURPOSE: The proportion of gastroesophageal junction adenocarcinoma is increasing. This study evaluated trends in early-onset gastric and esophageal cancers and compared socioeconomic and clinical characteristics between early-onset versus late-onset disease. MATERIALS AND METHODS: We included all patients with gastric and esophageal cancer from 2004 to 2015 from the National Cancer Database. Patients were categorized by age < 50, 50-69, and ≥ 70 years. Differences in pathologic and socioeconomic factors be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
(87 reference statements)
1
8
0
Order By: Relevance
“…We found that patients with EOGC were more likely to be female, Asian/PI, AA, Hispanic, uninsured, and present with stage IV disease versus patients with AOGC and LOGC. Our analysis was consistent with others that showed EOGC is more common in females, more likely to be diagnosed at an advanced stage and have a disproportionate effect on uninsured patients, African Americans, and Hispanic patients [ 13 , 14 , 15 , 16 ]. Others have shown that EOGC displays unique genomic features.…”
Section: Discussionsupporting
confidence: 92%
“…We found that patients with EOGC were more likely to be female, Asian/PI, AA, Hispanic, uninsured, and present with stage IV disease versus patients with AOGC and LOGC. Our analysis was consistent with others that showed EOGC is more common in females, more likely to be diagnosed at an advanced stage and have a disproportionate effect on uninsured patients, African Americans, and Hispanic patients [ 13 , 14 , 15 , 16 ]. Others have shown that EOGC displays unique genomic features.…”
Section: Discussionsupporting
confidence: 92%
“…These findings can broaden disparities in outcomes of patients with gastric cancer. Further, in this special series, the manuscript by Torrejon et al 7 adds to the body of evidence reporting increasing trends in early-onset gastric cancer (ie, diagnosed in young adults age < 50 years) over time using a national sample of patients with cancer. Specifically, Torrejon et al 7 highlighted the disproportionate burden of gastric cancer among Hispanic patients, who are known to have two times the risk of being diagnosed with gastric cancer compared with non-Hispanic White patients and are more commonly diagnosed with advanced cancer stages.…”
mentioning
confidence: 96%
“…Further, in this special series, the manuscript by Torrejon et al 7 adds to the body of evidence reporting increasing trends in early-onset gastric cancer (ie, diagnosed in young adults age < 50 years) over time using a national sample of patients with cancer. Specifically, Torrejon et al 7 highlighted the disproportionate burden of gastric cancer among Hispanic patients, who are known to have two times the risk of being diagnosed with gastric cancer compared with non-Hispanic White patients and are more commonly diagnosed with advanced cancer stages. 8,9 In the South Texas region, younger patients have significantly higher odds of advanced gastric cancer stage at diagnosis; specifically, patients age 20-29 years are nearly 4 times more likely to be diagnosed with advanced stage compared with those age 65 years or older.…”
mentioning
confidence: 96%
“…Similarly, in their paper on evaluating access and resources, Franco et al 3 note the impact of Affordable Care Act in reducing health care access barriers but with disproportionate and continuous chronic health problems in the Hispanic/Latinx patient population. Access to care was also noted as a challenge in the manuscript by Torrejon et al and was underlined for the patients who live in the border counties as reported by LaPelusa et al and Ju et al 4-6 In their papers, gaps in care for patients with colorectal and gastric cancer were noted with higher incidence, lower likelihood to receive guideline-concordant care, and worse survival for Hispanic/Latinx patients who live in the border counties. The editorial by Nodora and Velazquez 7 summarized the efforts and resources in Texas to evaluate and address the potential ways that we can achieve quality care in border counties.…”
mentioning
confidence: 97%
“…City of Hope, Duarte, CA2 Dana Farber Community Cancer Care-Lawrence, Boston, MA3 University of Miami, Coral Gables, FL4 Gilead Sciences, Clinical Development, Foster City, CA CORRESPONDING AUTHOR Linda D. Bosserman, MD, City of Hope, c/o 3803 Seashore Dr, Newport Beach, CA; e-mail: lbosserman@coh.org.…”
mentioning
confidence: 99%